Reformulating Islamic Digital Finance Regulation in the Contemporary Era: Toward Inclusive and Sustainable Development in Indonesia - Solikhah Solikhah; Burhanudin Harahap; Zeni Lutfiyah; Luthfiyah Trini Hastuti; Nur Sulistiyaningsih; Muhamad Abduh (Jurnal Ilmiah Mizani: Wacana Hukum, Ekonomi Dan Keagamaan, 2025)
This study examines the contemporary reformulation of Islamic digital finance regulation in Indonesia amid the rapid expansion of technology-driven financial services. The acceleration of digitalisation has created new opportunities for efficiency and financial inclusion, yet it also introduces regulatory challenges—particularly the low level of Islamic financial literacy and limited public understanding of Sharia principles embedded in digital financial products. Employing a normative legal research approach through statute and conceptual analyses, this study evaluates the alignment between the Financial Services Authority Regulation Number 40 of 2024 on Information Technology-Based Joint Funding Services and the National Sharia Council–Indonesian Ulema Council Fatwa Number 117/DSN-MUI/II/2018, which allows conventional business units to establish Sharia units, a provision previously restricted under Financial Services Authority Regulation Number 10 of 2022. The findings demonstrate that legal certainty, regulatory coherence, and innovation in Islamic digital financial products significantly shape the sector's development. Furthermore, the study proposes a model for a Sharia governance regulatory framework to strengthen good governance and ensure full compliance with Sharia principles. The research concludes that effective collaboration among the government, financial authorities, Islamic financial institutions, and the public is essential to enhancing the contribution of Islamic digital finance toward inclusive and sustainable development in Indonesia through continuous regulatory reform and ecosystem strengthening. Academically, this research contributes by proposing a contextual model for reformulating Islamic digital finance regulation in Indonesia, strengthening the conceptual linkage between statutory provisions and Sharia normative frameworks in fintech governance, and enriching scholarly debates on the role of Islamic digital finance as a driver of inclusive and sustainable development.